Childbirth and perinatality: The role of the hospital psychologist in this context (Research, Society and Development, 2021)
Psychological assistance carried out in the context of hospitals, clinics and health centers must cover the three pillars existing in the hospital environment, namely, patients, family members and health professionals. The specialist psychologist in the hospital modality can act on several fronts, including individual care and in psychotherapeutic groups, outpatient care and intensive care units (ICUs), wards, emergency care, diagnostic assessments, psychodiagnostics and consultancies. Even though several studies that talk about hospital psychology are identified, especially with regard to working with the patient, little is said about this front in the context of childbirth and perinatality. That said, this article aims to talk about the role of the psychologist in this context. It is justified because it is a relevant study, with little literature on the subject, which seeks to work on the importance of the psychologist not only in the treatment of patients, but also in the health promotion of parturient women. It is a qualitative study, with bibliographic survey done in online databases. The findings suggest that although the psychologist is inserted in the hospital context, his insertion in obstetric centers is not yet fully effective. It is concluded, therefore, that there is still a long way to build psychological practices to support families and, in particular, parturients, before, during and after childbirth, as well as a space within the obstetric / hospital environment for the psychology professional. Furthermore, it is emphasized the importance of research and studies dedicated to the theme, which corroborate for the construction of protocols related to psychological care in the hospital obstetric context.